PENGARUH GOOD CORPORATE GOVERNANCE (GCG), KUALITAS ASET DAN EFISIENSI TERHADAP PROFITABILITAS PADA BANK SYARIAH DI INDONESIA - Anggraeni, Anggraeni; Giranti, Oktaviana (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
Return on Assets (ROA) is one indicator to measure the company's ability to generate profits from all assets used. This study aims to determine the effect of total commissioners, the proportion of independent commissioners, government ownership, foreign ownership, NPF, BOPO and Size on ROA simultaneously and partially. This study uses secondary data from Islamic Commercial Banks, from 2010-2020. The sample of this study is eleven Islamic commercial banks that have been operating from 2010 to 2020. This study uses SPSS version 26. The results show that the total commissioners, the proportion of independent commissioners, government ownership, foreign ownership, NPF, BOPO and Size have a significant effect on ROA. Independent commissioners, government ownership and foreign ownership partially have a negative and insignificant effect on ROA. NPF and BOPO partially significant negative effect on ROA. Total commissioners and Size partially have a positive and not significant effect on ROA.